2019
DOI: 10.21873/cgp.20157
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Both USP10 and p14ARF Protein Expression Is an Independent Prognostic Biomarker for Poor Prognosis in Patients With Epithelial Ovarian Cancer

Abstract: Background/Aim: The prognostic role of USP10 in epithelial ovarian cancer has been studied in various human cancers. Our aim was to evaluate the clinical and pathological significance of USP10 in epithelial ovarian cancer. Materials and Methods: Immunohistochemical analyses of the expression of USP10 and p14ARF by using tissue microarrays were performed in 336 ovarian tumours and the data were compared with clinicopathological variables. We examined their level of DNA methylation around the putative transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…mRNA levels for G3BP1 , TIA-1 , TIAR , and CAPRIN-1 are mostly upregulated ( p ≤ 1.07 × 10 −4 ) in primary tumors when compared to healthy tissues ( Figures S1–S3 ). This correlates with observations made in several patient cohorts, where SGs proteins were upregulated in tumor as compared to healthy tissues [ 64 , 65 , 68 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Even if other possibilities exist to explain this phenomenon, we can hypothesize that tumor cells divert and exacerbate a pro-survival mechanism potentially based on SGs, in order to facilitate their survival in response to the numerous stresses encountered.…”
Section: Sgs Proteins As Prognostic Markers: At the Mrna Or Proteisupporting
confidence: 89%
See 1 more Smart Citation
“…mRNA levels for G3BP1 , TIA-1 , TIAR , and CAPRIN-1 are mostly upregulated ( p ≤ 1.07 × 10 −4 ) in primary tumors when compared to healthy tissues ( Figures S1–S3 ). This correlates with observations made in several patient cohorts, where SGs proteins were upregulated in tumor as compared to healthy tissues [ 64 , 65 , 68 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Even if other possibilities exist to explain this phenomenon, we can hypothesize that tumor cells divert and exacerbate a pro-survival mechanism potentially based on SGs, in order to facilitate their survival in response to the numerous stresses encountered.…”
Section: Sgs Proteins As Prognostic Markers: At the Mrna Or Proteisupporting
confidence: 89%
“…A high expression of CAPRIN-1 protein correlates with poor prognosis for patients with osteosarcoma [ 146 ], and hepatocellular carcinoma [ 147 , 148 ]. Consistent with an inhibitory effect of USP10 on SGs formation, high protein expression correlates with better prognosis in patients with ovarian [ 150 ], lung [ 151 ], small intestine [ 152 ], prostate [ 142 ], and stomach carcinoma [ 149 ] ( Table 1 ).…”
Section: Sgs Proteins As Prognostic Markers: At the Mrna Or Proteimentioning
confidence: 65%
“…A recent study has shown that MAPK9 activity played an indispensable part in invasiveness and BRAFi resistance of melanoma cell ( 47 ). As for USP10, decreased expression of USP10 has been proved to be an indicator of poor prognosis in lung cancer and epithelial ovarian cancer ( 48 , 49 ). Moreover, numerous studies have demonstrated that USP10 inhibited mTOR activation and promoted oncogene-induced senescence to exert a tumor-suppressive effect ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed that loss of USP10 (and p14ARF) expression is associated with tumor progression and poor prognosis in epithelial ovarian cancer; USP10 knockdown in ovarian cancer cells led to increased proliferation and clonogenicity 79 . In patients with small intestinal adenocarcinoma, loss of USP10 and p14ARF is associated with poor prognosis.…”
Section: Usp10 and Cancermentioning
confidence: 99%